Peran Kader Posyandu dalam Pengembangan Kesehatan Masyarakat di Desa Cemengbakalan Kecamatan Sidoarjo - Eka Lailatul Safitri; Hendra Sukmana (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to find out and describe the existing facts so that a clear picture is found of the role of posyandu cadres in the development of public health in Cemengbakalan Village. The research method uses descriptive qualitative type. This study uses primary and secondary data types. Explaining more clearly the role of posyandu cadres in Cemengbakalan Village to support community health development is the focus of this research. Sources of data obtained through interviews with cadres who play an active role in posyandu activities, records, and archival documentation. The results of the study prove that the role of posyandu cadres in the development of public health in Cemengbakalan Village is achieved by considering the role theory by Soekanto in which the roles are divided into three parts, namely active roles, participatory roles and passive roles. First, the active role, the finding of the active role of posyandu cadres in Cemengbakalan Village which is considered to have been achieved. Second, the participatory role of posyandu cadres in participating in posyandu activities has been declared to have been achieved. Third, the passive role of cemengbakalan posyandu cadres is declared not optimal because there is still a decline in the number of posyandu visits.